ANALISIS ISI FILM LUCKY KUSWANDI: SEBUAH TINJAUAN BEN-TUK KEKERASAN SEKSUAL DALAM FILM “DEAR DAVID” - Balqis Nadya Purbandari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The emergence of many digital platforms for watching films in this era shows that the level of public interest in films is increasing. This high trend certainly has implications for the increasing number of film genres circulating in society. Netflix has become a global streaming platform that can be accessed in Indonesia since January 2016 by offering films and television programs, including several programs created by Netflix which are usually called Original Netflix (Wikipedia, 2019). Dear David is a Netflix Original film with the romantic fantasy drama genre, which will be released in early 2023, directed by Lucky Kuswandy. The film Dear David reaped a lot of debate, because this film contains elements of female sexuality and sexual fantasy. Tells the story of a high school teenager who is involved in a sexuality case through writing on a personal digital platform. The main character named Laras, Laras is a high school student who gets an achievement scholarship at his school. Apart from excelling academically, Laras is also the student council president and is well-known for being involved in other social activities such as being active in Church activities. Laras' good image is destroyed, because his personal platform contains vulgar fantasy stories for a schoolmate he likes named David spread by his class mates. The purpose of this study is to identify and explain the forms of sexual violence that occur in the film Dear David. Film as a medium that influences people's mindsets makes this study interesting to write about. The research method used is quantitative content analysis method. The results of this study indicated that there was sexual violence in the form of physical sexual violence and non-physical violence. Non-physical sexual violence included: sexual comments (95%); flirt (100%); jokes (95%); whistle (89%); body gestures (100%); asking questions of a sexual nature (80%); stares lustfully (75%); gestures with fingers (66%); lip biting (100%); sexual object 987%); and peeping (80%). Physical sexual violence included: kissing (91%); stroked (100%); attaching the body (120%); looking at sensitive body parts (80%); and other physical touch (100%).